The dynamics of fast food consumption in a South African urban township environment - Mafame, Thendo (2019)
The delineation of ethnographic qualitative research methods allowed for this study to explore the dynamics of fast food consumption in the South African urban township environment. This study aimed to investigate the factors that influence the consumption of fast food. The research question states what factors in the urban township environment create increased fast food consumption and decreased consumption of traditional foods which are healthier and more nutritious.